Community Service Program on Innovative Digital Content for Elementary School Teachers to Strengthen the Pancasila Student Profile - Passalo, Nurfaizah Andi; Hotimah; Amin, Muhammad; Nurhaedah; Amrah (Pascasarjana Universitas Mataram, 2025)
This Community Service Program (PKM) aims to enhance the abilities of elementary school teachers in developing innovative digital content to support learning based on the values of the Pancasila Student Profile. The program is implemented through three main stages: socialization, intensive training, and evaluation. The first stage is the program socialization, which introduces the background, objectives, benefits, and mechanisms of the activity to the teachers and stakeholders in the target area. Subsequently, intensive training is conducted over two days with a practical approach, where teachers are trained to use digital tools such as the Canva design application, microsite creation using s.id, and the utilization of Augmented Reality (AR) technology to create engaging and relevant learning content aligned with the values of Pancasila. This training is participatory and collaborative, with direct guidance from education experts. Evaluation at the end of the program is carried out using feedback questionnaires. The evaluation results indicate that the training successfully improved the teachers' digital skills and their understanding of integrating Pancasila character values into learning media. This program is expected to serve as a training model that can be applied in other regions and support the transformation of education through technology and character-based learning in elementary schools.